The Implementation of User Centered Design Method in Developing UI/UX - Muktamar B, Ahmad; Lumingkewas, Cindy Sandra; Rofi'i, Agus (Journal of Information System, Technology and Engineering, 2023)
The university has an academic information system called AIS, of which students are one of the main users. Based on the results of the questionnaire from previous research, it has been proven that the AIS display still needs development. This research develops the UI/UX of AIS to better suit the needs of users with the UCD method. Starting from planning agreements with parties related to research, determining the context by interviewing parties who agreed in the first stage, determining needs with questionnaires to users, using the System Usability Scale (SUS) method to determine the results, designing a prototype based on the results of the third step, and UI/UX evaluation, which is carried out using the same method when evaluating the UI/UX AIS running in the third stage to prove whether there has been a significant improvement or not. The evaluation results show that there is an increase in UI/UX, and based on statistical tests, there is a significant difference between the current UI/UX AIS and the UI/UX AIS being developed. In the process of evaluation and statistical tests, even though the SUS calculation results were still marginal, the two AIS questionnaire results proved to have significant differences. So that the results of this study can be accepted, improvements can be made in the future.